Filoviruses A Compendium of 40 Years of Epidemiological, Clinical, and Laboratory Studies - Kuhn, Jens.; Calisher, Charles H.; SpringerLink (Online service) (Vienna : Springer Vienna : Imprint: Springer, 2008)
The filoviruses (Lake Victoria marburgvirus and ebolaviruses) are etiological agents of severe hemorrhagic fevers with extraordinary high case-fatality rates for humans, chimpanzees, gorillas, and probably other animals. Many institutions and experts consider them as potential threats to humanity because they could be used as biological weapons. This book summarizes in detail the contemporary knowledge of filoviruses and diseases they cause. Almost the entirety of the open literature on filoviruses, covering all major scientific and clinical fields, is referenced and summarized in this text, including most of the conference abstracts, book chapters, dissertations, government reports, patents, theses, and journal publications in many languages. The book will provide a robust source of knowledge for filovirologists, virologists and scientists in general, clinicians, students, journalists, and biodefense professionals.  .
History of filoviral disease outbreaks -- Clinical presentation of filoviral disease -- Filoviral disease pathology -- Geographic distribution of filoviruses: serological surveys -- Ecology of filoviruses: search for reservoirs -- Cultivation of filoviruses -- Molecular characteristics of filoviruses -- Laboratory diagnosis of filoviral disease -- Outbreak containment -- Inactivation of filoviruses and disinfection protocols -- Vaccine development -- Treatment of filoviral disease -- Appendix: Members of the Filoviridae Study Group, ICTV.
Keywords: Virology; Medical microbiology; Infectious diseases; Tropical medicine; Virology; Medical Microbiology; Infectious Diseases; Tropical Medicine